THE INFLUENCE OF PROBLEM SOLVING LEARNING STRATEGIES ON STUDENT LEARNING OUTCOES SMPN.15 KOTA PADANG - Adek Fakhri syah; Khairil Arif; Arief Muttaqiin; Rani Oktavia (SEMESTA: Journal of Science Education and Teaching, 2023)
The development of the times requires every country to have rapid progress. Good education produces quality human resources. The influence of education plays a very important role in the human resources produced. Education continues to change according to the times. Innovation continues to be carried out in order to provide better quality education, both in learning models and learning strategies. Learning carried out by schools does not only focus on models but must choose the right strategy where students are trained to independently seek and find solutions to each problem found in learning. One strategy that can be applied in learning is problem solving learning strategies. Type of Quasi-Experimental research or quasi-experimental research. This Quasi Experimental Research aims to see whether or not there is an effect of giving certain treatments to the study group. The research design that will be used is a Pretest-Posttest control group design. The sampling technique uses purposive sampling. The sample consisted of an experimental class applying problem solving learning strategies and a control class applying conventional learning models. Based on hypothesis testing which has been carried out with the help of Microsoft Excel using the U test technique with a significance level of 5%. The obtained values ​​for are -4.67 and -1.96. Then H₁ is accepted and H₀ is rejected. Based on these data, it can be concluded that the use of problem solving learning strategies influences the learning outcomes of students at SMP Negeri 15 Padang City.